Networking in gendered regional development - Mona Hedfeldt; Gun Hedlund (European Regional Science Association (ERSA), 2010)
The present Swedish regionalization process creates a lack of institutionalisation called the "regional mess" (Stegmann McCallion 2008:587). According to a state investigation, Sweden has a "fragmented growth- and development policy as well as a weak and unclear regional organisation of society" (SOU 2007:10:18). Old and new structures are intertwined and the question emerges if this situation may create a space for women regarding regional development (Hedfeldt & Hedlund 2009). A multi-level governance perspective (Hedlund & Montin 2009) shows how agents on different levels from EU to local municipalities seem to share the same policy regarding gender and regional development: an increase in women entrepreneurs. The formal alliance between women from different spheres seems to be weak regarding the EU structural fund partnerships (Hedfeldt & Hedlund 2009). If there are more developed networks on local and regional level remains to be investigated. Are there informal gendered networks on different levels which may create a path to gate-keepers or gate-openers for women to gain access to economic resources aimed for innovation, entrepreneurship and regional development? The aim of this paper is to study what kind of gendered networking exists in four different regions regarding the policy objective to increase the share of women in entrepreneurship. Our ambition is to apply a multiscientific approach where network theory from both human geography and political science are combined (Hanson 2000; Bang & Esmark 2009). Our data indicate that women entrepreneurs participate in structural funds projects and are involved through networking. On what terms do they participate? And when are they excluded? We study the networking between local and regional elected officials, business representatives, entrepreneurs, public servants and CGO' s, HNGO's and NGO's regarding different project for funding to support or strengthen women as entrepreneurs. The methods used are document studies, a survey to members in structural fund partnerships and interviews.
Keywords: 330